2021
DOI: 10.1136/jech-2021-216661
|View full text |Cite
|
Sign up to set email alerts
|

Prospective association between receipt of the economic impact payment and mental health outcomes

Abstract: BackgroundThe Coronavirus Aid, Relief, and Economic Security Act of 2020 provided ‘economic impact payments’ (EIPs) of $1200 to US adults with annual personal income of $75 000 or less. This study examined the prospective association between EIP receipt and mental health outcomes.MethodsA nationally representative sample of 3169 middle-income and low-income US adults completed a baseline assessment of their health and well-being in May–June 2020 and a 3-month follow-up assessment during the period of the COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…Com isso, os trabalhadores foram submetidos a interrupção das atividades laborais sem planejamento prévio ou reservas econômicas, resultando na perda financeira e no desenvolvimento de sintomas psicológicos capazes de interferir no funcionamento familiar e nos níveis de saúde mental. (28) A baixa escolaridade também associada ao comportamento suicida constitui um dos marcadores socioeconômicos e reflete as limitações no sistema educacional do Brasil para inclusão das pessoas com transtorno mental, assim como os comprometimentos psicológicos, comportamentais e cognitivos acarretados pelo transtorno mental que dificultam o acesso às práticas de ensino. (29,30) Ainda, destaca-se nesta investigação a subnotificação da tentativa de suicídio, demonstrando falhas no estabelecimento de indicadores epidemiológicos e na estruturação de programas para vigilância, monitoramento de casos e prevenção.…”
Section: Discussionunclassified
“…Com isso, os trabalhadores foram submetidos a interrupção das atividades laborais sem planejamento prévio ou reservas econômicas, resultando na perda financeira e no desenvolvimento de sintomas psicológicos capazes de interferir no funcionamento familiar e nos níveis de saúde mental. (28) A baixa escolaridade também associada ao comportamento suicida constitui um dos marcadores socioeconômicos e reflete as limitações no sistema educacional do Brasil para inclusão das pessoas com transtorno mental, assim como os comprometimentos psicológicos, comportamentais e cognitivos acarretados pelo transtorno mental que dificultam o acesso às práticas de ensino. (29,30) Ainda, destaca-se nesta investigação a subnotificação da tentativa de suicídio, demonstrando falhas no estabelecimento de indicadores epidemiológicos e na estruturação de programas para vigilância, monitoramento de casos e prevenção.…”
Section: Discussionunclassified
“… Watson et al, (2020) found a 14% increase in substance-abuse incidents the day after the Alaska's Permanent Fund Dividend payment and a 10% increase over the following four weeks. Regarding the economic impact payments, Tsai et al, (2021) found that those that first received the economic impact payment during the COVID-19 pandemic had a significantly increased use of any illicit drug in the past month. When taken into consideration with the previously identified COVID-19 policy impact on PWOUD such as social isolation, loss of income/ housing, reduced availability of harm reduction strategies and decreased access to MOUD ( Henderson et al, 2021 ), the sudden infusion of economic resources created by the economic impact payments may have also played a contributing role in the exacerbation of the opioid epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…This included child benefit in the U.K., Canadian child benefits in Canada, child tax benefit in South Korea, and child allowance in Japan, among many others. A growing body of COVID-19 studies in the U.S. has also found that there are relationships between income supplements and mental health, such as stimulus checks [17], economic impact payment [18], unemployment insurance [19], supplemental nutrition assistance programs [20], and temporary assistance for needy families [21,22], among many others. Focusing on child mental health, studies identified the positive role of cash assistance.…”
Section: Expansion Of the Us Child Tax Credit Amid The Crisis Of Ment...mentioning
confidence: 99%